University Studies of Henrik Marczali (Morgenstern) - Tóth, Krisztina (Per Aspera ad Astra, 2025)
Henrik Marczali was a student at the University of Pest (now Eötvös Loránd University) between 1870 and 1875. His years as a student at the university were the years when the university was undergoing a major transformation, and he became an active participant in this change. He was among the first to be admitted to the newly established Teacher Training Institute, and although he began his studies under the old system, he completed his doctorate under the new regulations introduced in 1873. However, the transformation was not only at the organisational level, the teaching staff was also renewed, and in 1870 or in the few years before, influential teaching personalities began their careers at the university, who shaped Henrik Marczali’s interests, his later methods and character as a historian. He had three outstanding, character-shaping teachers in the persons of János Hunfalvy, Mór Kármán and Árpád Kerékgyártó. They have tried to develop Marczali’s talent and excellent qualities, and to correct his faults – especially his stubbornness and scatteredness. Thanks to Árpád Kerékgyártó, detailed reports have been preserved on the teaching at the Teacher Training Institute and the work of the students, including Henrik Marczali. This paper will present Marczali’s student years, his professors and the changing university education through his memoirs and archival sources.